If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 2) = -2(x + 6) Reorder the terms: 2(2 + x) = -2(x + 6) (2 * 2 + x * 2) = -2(x + 6) (4 + 2x) = -2(x + 6) Reorder the terms: 4 + 2x = -2(6 + x) 4 + 2x = (6 * -2 + x * -2) 4 + 2x = (-12 + -2x) Solving 4 + 2x = -12 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 4 + 2x + 2x = -12 + -2x + 2x Combine like terms: 2x + 2x = 4x 4 + 4x = -12 + -2x + 2x Combine like terms: -2x + 2x = 0 4 + 4x = -12 + 0 4 + 4x = -12 Add '-4' to each side of the equation. 4 + -4 + 4x = -12 + -4 Combine like terms: 4 + -4 = 0 0 + 4x = -12 + -4 4x = -12 + -4 Combine like terms: -12 + -4 = -16 4x = -16 Divide each side by '4'. x = -4 Simplifying x = -4
| 44=x(5+6) | | 7x-(2x+5)=36 | | 2w-36=w-12 | | 46*7+87*3+21*3= | | W-12=2w-36 | | 1/3✖️3/4 | | 1/3✖️3/4=3/8 | | 29*7+16*3+8*3= | | 6y-14=9y-5 | | -3(y+2)=7y-8+4(2y+4) | | .027+2-.035x=0 | | 540*10+160*3= | | 3s-36=5s-88 | | .027+2=.035x | | -4x+10y=12 | | 15.5-7.9= | | .66(-12c+6)-7c+2c-6= | | 4m-6/5=-3 | | 16.1+6.1= | | -17+2=2x-2x-3x | | b-.25=3.5 | | 16.1-22= | | 3/8-x/4=1/16 | | 12(3x+6)(x-2)=0 | | 3y-76=-40 | | -1y-4y+8y=-6+6 | | -(d-2)= | | (X^2+36)+x^2=3600 | | 3q-17=q-1 | | 3/4*x=61.5 | | (5x+10)/5+2x=10+1 | | 11.4-4z=-10 |